Encrypting Secret Information inside an Image Using Steganography - Bhardwaj, Udita; Singhal, Vikas; Dubey, Shivani (International Journal of Computer Sciences and Engineering, 2023)
Converting information into the image format has become the latest method which can be implemented for encrypting information into colours. Experts have projected different methods to implement this approach to secure data against hackers. Most of the approaches square measuring readily implemented algorithms or putting forward an easy level of the coding execution which makes these methods a risk to break by attackers. A new and emerging method of operations is discussed through this paper so as to build a word-To-picture encrypting approach. The substitution and transposition operations square measure applied into two levels ((characters (bytes) and bits) of the written information to formulate the secret and safe image. Together the given functions provide lots of strength points to fight against hackers. The projected method has been applied and verified across various sets of information; the recorded observations proved the efficiency and correctness of the methodology as an efficient Text-To-Image encrypting approach.